Auxiliary subunits of the CKAMP family differentially modulate AMPA receptor properties - Farrow, Paul; Khodosevich, Konstantin; Sapir, Yechiam; Schulmann, Anton; Aslam, Muhammad; Stern-Bach, Yael; Monyer, Hannah; Engelhardt, Jakob von (eLife, 2015)
AMPA receptor (AMPAR) function is modulated by auxiliary subunits. Here, we report on three AMPAR interacting proteins - namely CKAMP39, CKAMP52 and CKAMP59 - that, together with the previously characterized CKAMP44, constitute a novel family of auxiliary subunits distinct from other families of AMPAR interacting proteins. The new members of the CKAMP family display distinct regional and developmental expression profiles in the mouse brain. Notably, despite their structural similarities they exert diverse modulation on AMPAR gating by influencing deactivation, desensitization and recovery from desensitization, as well as glutamate and cyclothiazide potency to AMPARs. This study indicates that AMPAR function is very precisely controlled by the cell-type specific expression of the CKAMP family members.